2012
DOI: 10.1111/j.1523-5378.2012.00970.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of H. pylori Infection with Insulin Resistance and Metabolic Syndrome Among Lebanese Adults

Abstract: Prevalence of H. pylori infection in Lebanon is comparable to other developing countries. Furthermore, our findings suggested no association of H. pylori infection with IR or MetS. Eradication of H. pylori infection to prevent IR or MetS is not warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
9
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 38 publications
9
54
9
3
Order By: Relevance
“…This number is in line with the three previously conducted studies in Lebanon that estimated the prevalence between 21% and 52% [13][14][15]. In our study we found no difference in H. pylori prevalence between the sexes.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This number is in line with the three previously conducted studies in Lebanon that estimated the prevalence between 21% and 52% [13][14][15]. In our study we found no difference in H. pylori prevalence between the sexes.…”
Section: Discussionsupporting
confidence: 82%
“…In our study we found no significant association between H. pylori and diabetes (p=0.979). This is in line with a study done by Naja et al on the association of H. pylori infection with insulin resistance and metabolic syndrome (MetS) among Lebanese adults that found no association of H. pylori infection with IR or MetS, and concluded that the eradication of H. pylori infection to prevent IR or MetS is not warranted [15].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Multiple animal and human studies were performed over the years in order to understand the links between Hp and T2DM [15][16][17].…”
Section: Metabolic Changes In Hp With T2dmmentioning
confidence: 99%